Memanfaatkan Limbah Sedotan Plastik Menjadi Vas Bunga Hias - Halimatusa’diyah, Enni; Fadhila, Puan; Amirah, Nurul (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This journal was created to learn how to make flower vases from plastic straws. A descriptive qualitative research methodology was applied in this literature review type of research. The results show that the use of plastic waste to make flower vases is one way to reduce the amount of plastic waste in the environment because plastic waste cannot decompose. By using plastic waste as the basic material for making flower vases, plastic waste can be reused and prevent the accumulation of plastic waste in the environment.